2021
DOI: 10.7554/elife.55070
|View full text |Cite
|
Sign up to set email alerts
|

Co-regulation and function of FOXM1/RHNO1 bidirectional genes in cancer

Abstract: The FOXM1 transcription factor is an oncoprotein and a top biomarker of poor prognosis in human cancer. Overexpression and activation of FOXM1 is frequent in high-grade serous carcinoma (HGSC), the most common and lethal form of human ovarian cancer, and is linked to copy number gains at chromosome 12p13.33. We show that FOXM1 is co-amplified and co-expressed with RHNO1, a gene involved in the ATR-Chk1 signaling pathway that functions in the DNA replication stress response. We demonstrate that FOXM1 and RHNO1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 138 publications
(249 reference statements)
2
11
0
Order By: Relevance
“…In HGSC patients, shallow whole genome sequencing (sWGS) of circulating tumor DNA (ctDNA) from plasma revealed a 16% increase in chromosome 12p13.33 amplification (location of FOXM1 ) after the acquisition of chemotherapy resistance [ 128 ]. In agreement, we observed that almost half of HGSC patients have increased FOXM1 expression in recurrent chemoresistant tumors [ 256 ]. Bioinformatic analysis led to the identification of FOXM1 as one of the top three hub genes for which overexpression leads to platinum-based chemotherapy resistance [ 257 ].…”
Section: Foxm1 Oncogenic Functionssupporting
confidence: 77%
See 2 more Smart Citations
“…In HGSC patients, shallow whole genome sequencing (sWGS) of circulating tumor DNA (ctDNA) from plasma revealed a 16% increase in chromosome 12p13.33 amplification (location of FOXM1 ) after the acquisition of chemotherapy resistance [ 128 ]. In agreement, we observed that almost half of HGSC patients have increased FOXM1 expression in recurrent chemoresistant tumors [ 256 ]. Bioinformatic analysis led to the identification of FOXM1 as one of the top three hub genes for which overexpression leads to platinum-based chemotherapy resistance [ 257 ].…”
Section: Foxm1 Oncogenic Functionssupporting
confidence: 77%
“…We showed that RHNO1 , which encodes a DNA damage repair protein involved in the cellular RS response, shares a head-to-head (i.e., bidirectional) gene arrangement with FOXM1 on chromosome 12p13.33 [ 256 ]. Activation of the FOXM1/RHNO1 bidirectional promoter (F/R-BDP) leads to balanced gene expression of both genes and we observed that FOXM1 and RHNO1 each promote HGSC cell growth, survival, and homologous recombination (HR) DNA damage repair [ 256 ]. Importantly, FOXM1 and RHNO1 promoted olaparib and carboplatin resistance, and CRISPR-dCas9-mediated repression of the F/R-BDP reversed these effects [ 256 ].…”
Section: Foxm1 Oncogenic Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the potential use of the NB compounds in combination with relevant HGSC chemotherapies, we investigated the synergy between NB-73 or NB-115 with the platinum-based chemotherapy agent carboplatin or the poly (ADP-ribose) polymerase (PARP) inhibitor olaparib. Combinations with these chemotherapy agents are supported by the known role of FOXM1 in stimulating the expression of DNA repair genes 8 as well as our recent studies using genetic depletions of FOXM1 44 .…”
Section: Nb-73 and Nb-115 Synergize With Carboplatin To Impair Hgsc C...mentioning
confidence: 91%
“…Forkhead box M1 (FOXM1) is a transcription factor and a target of HuR [23], and overexpression and activation of FOXM1 is frequent and associated with worse prognosis in patients with HGSOC [24,25]. Moreover, FOXM1 overexpression also contributes to cell proliferation, cell cycle progression, chemoresistance, migration, and invasion in HGSOC [25][26][27].…”
Section: Foxm1 Which Is Regulated By Hur Contributes To the Anti-hgso...mentioning
confidence: 99%